Recognition of Prior Learning (RPL) Knowledge Claims: How can different types of knowledge be identified, documented and assessed in RPL applications of RPL credits. Comparison of two case studies at a South African vocational/professional higher educational institution (V/PHEI) - De Graaff, Frederika Hilde (School of Education, 2025)
The purpose of this study was to analyse the inner workings of RPL in the case of awarding credits for subjects within a qualification via RPL. For this study, RPL for credits requires the applicant to present informal and non-formal learning from the workplace in a manner that is recognisable within a higher education context. This qualitative study employed a case study methodology to highlight the uniqueness of two RPL applications: Human Resources Management and Architectural Technology. The RPL process at the institution is qualification-specific, with its RPL processes and requirements tailored to the qualification and its associated profession. Drawing on the concepts of different knowledge structures and disciplinary boundaries (Bernstein, 1999, 2000), knowledge from the formal qualifications was analysed, and the nature of the boundary in each knowledge field was explored. All documentation from the RPL process was analysed, and all academics involved were interviewed. To facilitate the RPL application, the academic departments changed the learning outcomes (LO) from the formal curriculum into RPL LOs for each qualification. A taxonomy based on the work of Anderson and Krathwohl (2002), consisting of two fields, type of knowledge and complexity of knowledge, was adopted as a conceptual tool to analyse and compare both sets of LOs. This study demonstrates that workplace knowledge can successfully be recognised for credits in an academic programme, under particular conditions. One enabling factor was that the knowledge structures of the disciplines concerned were found to be hybrid and segmented in nature. A further enabling factor was identified by drawing on the concept of 'chain of recontextualisation' (Evans et al., 2009). At least three interlinked processes o f recontextualisation were identified: Firstly, LOs from the formal curriculum were recontextualised into the RPL programme takes place; secondly, the RPL candidates recontextualised their workplace knowledge in the course of their portfolio development; and thirdly, the academics – in assessing the RPL application, interpreted (recontextualised) the evidence of workplace knowledge presented. The theoretical and knowledge contribution of this thesis includes that RPL for credit is not solely a process of Recognition of Prior Learning but also a process of Recontextualisation of Prior Learning (R-PL). The academics involved in the study adjusted and changed the learning outcomes of the formal programme for the purposes of the RPL programme. This demonstrates that selected learning outcomes of a formal programme need to be analysed and modified before an RPL process is undertaken. A further contribution is that this processes of recontextualisation points to the importance of a shared repertoire between the RPL assessors and the RPL applicants and highlights the significance of shared tacit knowledge (tacit-to-tacit knowledge) between RPL applicant and assessor within a specific field of expertise. The study demonstrates that granting credits via RPL is a complex process that requires a deep understanding of the curriculum, the workplace, the profession, and the legal framework within which the qualifications and RPL operate in South Africa. The conclusion supports Cooper and Ralph's (2016) view of RPL as a Specialised Pedagogy.